'Solemn Progress': Woolf, Burke, and the Negotiation of Virtue. Issue 3 (November 2017) - Zhang, Nan
Abstract : This essay analyzes Virginia Woolf's exploration of a public spirit exceeding both bourgeois egotism and narrow patriotic allegiances prescribed by the imperial state. Excavating hitherto unexamined affinities between Woolf and Edmund Burke, the essay shows how Woolf's vision of 'solemn progress' in Mrs Dalloway effectively conjoins a Burkean emphasis on the civilizing effects of aesthetic sentiments with a Renaissance humanist notion of virtù . Woolf's re-imagining of solidarity involves two moves that are temporally divergent yet temperamentally complementary: a renewal of attention to older conceptions of civil society whose ethic was civilized rather than narrowly civic; and an extension of the domain of society to a cosmic realm of life beyond the purview of the political state. By realigning public spirit with moral responses to a view of shared fate, Woolf seeks to relocate virtue in a collective experience across class and national boundaries.